A short review on lymphatic endothelial cell heterogeneity - Masayuki Miyasaka (Inflammation and Regeneration, 2021)
Abstract Recent single-cell RNA sequencing studies in mouse and human have clearly indicated that lymphatic endothelial cells (LECs) consist of multiple cell subsets, each expressing a unique set of genes, residing in distinct locations in the body. These studies have also revealed a conserved pattern of gene expression in LECs across animal species, as well as specialized sets of genes unique to each species. However, the extent to which this heterogeneity is adaptive to the external milieu surrounding LECs has remained unclear. The transcriptional and regulatory pathways that program the different subsets of LECs also remain unexplored.